AUTOMATED WORKSTATION FOR TRYOUT OF ESTIMATING ALGORITHMS OF POSITION OF AIRCRAFT UNDER APPROACH AND LANDING OPERATIONS - Kondrashov, Ya.; Fialkina, T.; Ryabets, O. (Science-based technologies, 2011)
For multiposition radio rangefinding navigation and landing system is justified and chosen method of mathemat-ical simulation  of  estimation  algorithms  o  location  of  the aircraft,  shown  the  hardware  and  software  structure for its implementation.